Macrosomic Newborn and Glucose Level in Lean Pregnant Diabetes Mellitus Patients at Dr. Soetomo General Hospital Surabaya - Sonea Venugopal; Hermanto Tri Joewono; Pudji Lestari (Althea Medical Journal, 2018)
Background: Gestational diabetes mellitus, defined as glucose intolerance in variable degree with onset during pregnancy, is a risk factor for the development of fetal macrosomia, a newborn with the birthweight of more than 4000g. The objective of this study was to explore an association between glucose level in lean pregnant diabetes mellitus patients, resulting in babies and the incidence of macrosomia in Dr Soetomo General Hospital in Surabaya.Methods: This was a retroprospective analytic study with a cross sectional design by using medical records at Dr. Soetomo General Hospital Surabaya, collected from January 2016 to December 2017. The correlation between fasting glucose level, 2-hour postprandial glucose and glucose level at the time of birth and weight of newborn was assessed.Results: Controlled and uncontrolled fasting glucose level, 2-hour postprandial glucose level and glucose level at the time of birth of mother were not significantly associated with macrosomia newborns. Macrosomia newborn were born with gestational diabetes mellitus mothers compare with pregestational mellitus mothers.Conclusions: There is no association between macrosomia with glucose level of lean gestational and pregestational diabetes mellitus, however, therapeutic approach such as physical exercise should be implemented to reduce effects of uncontrolled glucose level.